2017
DOI: 10.3382/ps/pew468
|View full text |Cite
|
Sign up to set email alerts
|

Expression of host defense peptides in the intestine of Eimeria-challenged chickens

Abstract: Avian coccidiosis is caused by the intracellular protozoan Eimeria, which produces intestinal lesions leading to weight gain depression. Current control methods include vaccination and anticoccidial drugs. An alternative approach involves modulating the immune system. The objective of this study was to profile the expression of host defense peptides such as avian beta-defensins (AvBDs) and liver expressed antimicrobial peptide 2 (LEAP2), which are part of the innate immune system. The mRNA expression of AvBD f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 30 publications
5
21
0
1
Order By: Relevance
“…These observations support the results of previous reports, showing that the AvBD genes were expressed in the small intestine and cecum of embryos and chicks (Akbari et al, 2008;Crhanova et al, 2011;Hong et al, 2012;Lu et al, 2015;Zang et al, 2016;Su et al, 2017;Terada et al, 2018). AvBD2 in the mucosal leukocytes (Terada et al, 2018) and AvBD9 in enteroendocrine cells from the luminal and crypt epithelia have also been reported (Cuperus et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…These observations support the results of previous reports, showing that the AvBD genes were expressed in the small intestine and cecum of embryos and chicks (Akbari et al, 2008;Crhanova et al, 2011;Hong et al, 2012;Lu et al, 2015;Zang et al, 2016;Su et al, 2017;Terada et al, 2018). AvBD2 in the mucosal leukocytes (Terada et al, 2018) and AvBD9 in enteroendocrine cells from the luminal and crypt epithelia have also been reported (Cuperus et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Accordingly, as observed in the current study, the expression of multiple AvBDs changed during the first week of life, and there seems to be an association between the colonization of natural or specific microbiota complexes and changes in AvBDs expressed during the early post-hatch period. However, challenge with specific microorganisms may cause an upregulation of AvBDs, as expression of AvBD8 and 13 in the cecum of 21-day-old broiler chickens was upregulated by Eimeria maxima (Su et al, 2017), and expression of AvBD1, 2, 4, and 6 was increased in the cecal tonsils of broiler chicks 3-5 days post infection by Salmonella Typhimurium, starting from 1 day of age (Akbari et al, 2008). The intestinal microbiota composition plays an important role in the maintenance of gut health (Clavijo and Flórez, 2018).…”
mentioning
confidence: 99%
“…The current study showed that the decline in AvBD expression in the post-hatch period occurs not only in the cecum, but also in the ileum. Su et al (2017) …”
mentioning
confidence: 99%
“…Intestinal tract is an important part of the body defense system and the main place for animal to digest and absorb the nutrients of feed [1,2]. The functions of poultry intestines are mainly carried out in the small intestine, which is also the longest part of the digestive tract [3].…”
Section: Introductionmentioning
confidence: 99%